The usefulness of a body shape index in assessing muscle function and strength in older adults hemodialysis patients - Knap, Bojan; Žvanut, Boštjan; Brezočnik, Lucija; Jurdana, Mihaela (Frontiers in Endocrinology, 2025)
ObjectiveThis study investigates the relationship between a new anthropometric measure, the Body Shape Index (ABSI), and body composition and biochemical parameters in hemodialysis patients and, for the first time, the correlation between ABSI and muscle strength and function in these patients.MethodsA cross-sectional study was conducted on a sample of 80 patients who were regularly treated in the hemodialysis unit of a single medical center of the University Hospital of Ljubljana, Slovenia. General anthropometric parameters body mass index (BMI) and ABSI=(WC/(BMI2/3x height½) as well as body composition data (fat mass FM, fat-free mass FFM, fat-free mass index FFMI, skeletal muscle index SMI) were determined in 25 women (aged 74.5 ± 7.5 years) and 55 men (aged 70.1 ± 6.6 years) with overweight (25 kg/m2 ≤ BMI < 30 kg/m2) and obesity (BMI ≥ 30 kg/m2) by bioelectrical impedance analysis (BIA). Muscle strength was determined using a hand grip strength test, while muscle performance was assessed using the sit-to-stand test.ResultsABSI was significantly negatively associated with muscle strength, functional tests and SMI only in men. Based on the median ABSI value (0.090273 m11/6·kg−2/3 in women and 0.090893 m11/6·kg−2/3 in men), women with a higher ABSI had a significantly higher glucose concentration than those with a lower ABSI. Men with a lower ABSI obtained significantly better results in the hand grip test, sit-to-stand test and waist circumference (WC).In conclusion, our findings suggest an inverse association between ABSI and muscle strength and function in male hemodialysis patients, indicating that higher ABSI may reflect poorer physical condition in this population. Further longitudinal studies are needed to explore the clinical significance of this relationship.